2003
DOI: 10.1086/378194
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Census ofHubble Space TelescopeCounterparts toChandraX‐Ray Sources in the Globular Cluster 47 Tucanae. II. Time Series and Analysis

Abstract: We report time series and variability information for the optical identifications of X-ray sources in 47 Tucanae reported in Paper I (at least 22 cataclysmic variables [CVs] and 29 active binaries). The radial distribution of the CVs is indistinguishable from that of the millisecond pulsars (MSPs) detected by Freire et al. A study of the eight CVs with secure orbital periods (two obtained from the Chandra study of Grindlay et al.) shows that the 47 Tuc CVs have fainter accretion disks, in the V band, than f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 43 publications
5
109
0
Order By: Relevance
“…Heinke et al (2005) used a deep Chandra observation of the cluster to perform a population analysis which concluded that there are likely ∼25 radio MSPs (<60 at 95% confidence) residing in the cluster, independent of beaming. Comparing this with optical and radio studies of the MSP population by Edmonds et al (2003) and McConnell et al (2004) respectively, who both conclude that the total MSP population in 47 Tuc is ∼30, Heinke et al (2005) conclude that the beaming fraction is > ∼ 37%. While these various studies suggest that the beaming fraction of MSPs is significantly larger than for normal pulsars, and could be quite high, we cannot strongly rule out beaming as the cause of our non-detection of 1RXS J141256.0+792204.…”
Section: Resultsmentioning
confidence: 54%
“…Heinke et al (2005) used a deep Chandra observation of the cluster to perform a population analysis which concluded that there are likely ∼25 radio MSPs (<60 at 95% confidence) residing in the cluster, independent of beaming. Comparing this with optical and radio studies of the MSP population by Edmonds et al (2003) and McConnell et al (2004) respectively, who both conclude that the total MSP population in 47 Tuc is ∼30, Heinke et al (2005) conclude that the beaming fraction is > ∼ 37%. While these various studies suggest that the beaming fraction of MSPs is significantly larger than for normal pulsars, and could be quite high, we cannot strongly rule out beaming as the cause of our non-detection of 1RXS J141256.0+792204.…”
Section: Resultsmentioning
confidence: 54%
“…Examples in 47 Tuc are the cases of the X-ray sources W42 (an accreting black hole candidate, Miller-Jones et al 2015) and W82 (a millisecond pulsar -MSP-, Bogdanov et al 2006) which were initially classified as CVs by Paresce et al (1992) and Edmonds et al (2003a, hereafter E03a), respectively. Although, we note that Edmonds et al 2003b (from now on E03b) also suggested that W82 could be an MSP. To mitigate the risk of misclassification, the combination of photometric information at different wavelengths is important.…”
Section: Introductionmentioning
confidence: 65%
“…We identified W96 as its X-ray counterpart. The possibility of W96 being an MSP was previously suggested by Edmonds et al (2003b), based on the lack of an optical Note-The BBODYRAD and NSATMOS models used CFLUX and the FLUX command respectively, to determine the unabsorbed luminosity. MSPs ab & S were fit with the χ 2 statistic (and the null hypothesis probability is quoted rather than the C-stat "goodness" statistic), the rest were fit with the C-statistic.…”
Section: Msp 47 Tuc Aamentioning
confidence: 99%